2015
DOI: 10.1002/j.0022-0337.2015.79.2.tb05867.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Comprehensive Care and Departmental Clinical Education Models: Students’ Perceptions at the University of Tennessee College of Dentistry

Abstract: In summer 2012, the University of Tennessee Health Science Center College of Dentistry transitioned from a departmental clinical education model to a comprehensive care/group leader model. The aim of this study was to investigate the perspectives of the fourth-year class of dental students who, because the transition took place during their training, had experienced treating patients under both educational models. To achieve this objective, a questionnaire was designed to assess the students' opinions on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 7 publications
1
16
0
2
Order By: Relevance
“…Like many U.S. dental schools over the last 25 years, the University of California, San Francisco (UCSF) School of Dentistry has employed various clinical curricula to ensure students obtain adequate clinical experience and attain required competencies for graduation. Dental schools have introduced such innovative curriculum and assessment formats as comprehensive care, 1 6 case completion, 7 , 8 competency examinations, 9 12 portfolios, 13 , 14 and community‐based, off‐campus externships 15 17 . UCSF has had three major clinical curricular changes since 1992, moving from a discipline‐based curriculum to a comprehensive care curriculum to a procedural requirement curriculum plus externships.…”
mentioning
confidence: 99%
“…Like many U.S. dental schools over the last 25 years, the University of California, San Francisco (UCSF) School of Dentistry has employed various clinical curricula to ensure students obtain adequate clinical experience and attain required competencies for graduation. Dental schools have introduced such innovative curriculum and assessment formats as comprehensive care, 1 6 case completion, 7 , 8 competency examinations, 9 12 portfolios, 13 , 14 and community‐based, off‐campus externships 15 17 . UCSF has had three major clinical curricular changes since 1992, moving from a discipline‐based curriculum to a comprehensive care curriculum to a procedural requirement curriculum plus externships.…”
mentioning
confidence: 99%
“…The student‐centred approach places a great deal of emphasis on students' educational needs, especially the completion of discipline‐specific procedural requirements . This approach has largely informed the traditional departmental, discipline‐based system of delivering CE . In this system, patients are assigned to students based on the students' educational needs and readiness to provide care .…”
Section: Traditional Ce Approaches and Systemsmentioning
confidence: 99%
“…Research shows that traditional approaches do not properly respond to the interplay of needs and interests of the stakeholders involved in CE . For instance, Dehghan et al found that whilst students valued the opportunity to provide more comprehensive care under the group practice system, they were concerned about not being exposed to the experiences of instructors and students outside of their group, which they recognised as an advantage of the student‐centred, discipline‐based system . Similarly, Park & Howell found that fourth‐year students favoured a case‐completion system informed by the patient‐centred approach over the traditional procedure‐based system; however, they recognised the insufficient exposure to some procedures as a limitation of the former system .…”
Section: Limitations Of Current Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…From one view, it enables students to look upon the greater image of treating patients and not to focus on one precise problem. Furthermore, patients' needs are met, and health care is provided in a proper sequential manner which is not applicable when a “student-centered approach” is practiced [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%